Multiple Crimean-Congo Hemorrhagic Fever Virus Strains Are Associated with Disease Outbreaks in Sudan, 2008–2009 - Aradaib, Imadeldin E. (Public Library of Science, 2011)
BACKGROUND: Crimean-Congo hemorrhagic fever (CCHF) activity has recently been detected in the Kordufan region of Sudan. Since 2008, several sporadic cases and nosocomial outbreaks associated with high case-fatality have been reported in villages and rural hospitals in the region. PRINCIPAL FINDINGS: In the present study, we describe a cluster of cases occurring in June 2009 in Dunkop village, Abyei District, South Kordufan, Sudan. Seven CCHF cases were involved in the outbreak; however, clinical specimens could be collected from only two patients, both of whom were confirmed as acute CCHF cases using CCHF-specific reverse transcriptase polymerase chain reaction (RT-PCR). Phylogenetic analysis of the complete S, M, and L segment sequences places the Abyei strain of CCHF virus in Group III, a virus group containing strains from various countries across Africa, including Sudan, South Africa, Mauritania, and Nigeria. The Abyei strain detected in 2009 is genetically distinct from the recently described 2008 Sudanese CCHF virus strains (Al-fulah 3 and 4), and the Abyei strain S and L segments closely match those of CCHF virus strain ArD39554 from Mauritania. CONCLUSIONS: The present investigation illustrates that multiple CCHF virus lineages are circulating in the Kordufan region of Sudan and are associated with recent outbreaks of the disease occurring during 2008–2009.